an Analysis of Logo’s as Found in Social Media Application: a Semiotics Study - Simbolon, Ester Wilis; Manik, Sondang; Sinambela, Erika (LPPPIPublishing, 2024)
Semiotics is the study of signs and symbols and how they are function and interpreted in communication. This Semiotic research aims to analyse logos found in social media applications using a semiotic approach from Roland Barthes' theory. Barthes' theory can explore how the visual elements in logos convey implied meaning. Descriptive qualitative methods were used in this research. Data sourced are taken from app store screenshots totally 35 logos and the author selected seven logo's. The research results show that logos on social media applications have visual signs. In terms of denotation, the music symbol logo depicts entertainment, the green circle with a telephone icon represents communication, or the triangle resembles a speech balloon which represents interaction. In the connotation meaning there is a deeper meaning and evokes an emotional response. For example, bright colors reflect passion and creativity, while blue can be seen as a symbol of trust and stability. After the denotational and connotative meanings are revealed. A myth is formed summarizing a broader cultural narrative. The myth of these logos represents self-expression and global connectedness and gives the impression that communication can be done quickly, safely and also spread trends quickly. This research reveals that logos on social media applications not only function as visual identifiers but also encapsulate deeper meanings and narratives that can be received by users. Each logo has a distinctive and unique design as a platform identity, and also contains emotional and cultural meaning, so it is more than just a visual sign.